Empower Peers 4 Careers: Positive Peer Culture to Prepare Adolescents’ Career Choices - Schellenberg, Claudia; Steinebach, Christoph; Krauss, Annette (Frontiers in Psychology, 2022)
For youth with special needs, where cognitive difficulties, behavioral and psychosocial issues are more common, career choice is particularly challenging. The Positive Peer Culture approach uses the resource of peer support to systematically build self- and social competencies. Important key elements are that adolescents feel safe to share their own problems and challenges with others, to overcome difficulties and challenges, to take responsibility for their lives, and to help each other. The Empower Peers 4 Careers Project aims to apply the PPC approach to the context of career choice to promote the development of important competencies for the transition from school to work. The pedagogical background of the Positive Peer Culture approach in the setting of career choice, as well as the required learning environments for the peers are presented. The peer group meetings are organized following a defined process through which learning forms social and personal competencies, career choice maturity as well as the class climate can be strengthened. In addition, the role of the moderators of the peer groups - such as class teachers or special education teachers - is examined in more detail and the concept is presented of how they are trained on topics such as resilience promotion and strengths orientation in the context of career choice preparation. The project "Empower Peers 4 Careers" is scientifically monitored over two years using a quasi-experimental control group design, which includes quantitative and qualitative methods. 15 classes of the 8th grade (age group: 14-year-olds) of regular and special schools as well as ten classes as control classes are participating. The results of the research and evaluation will not be available until 2023. The article presents the concept with the long-term goals, the implementation and didactics, as well as the hypotheses and the procedure for the evaluation.